If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8y + -16w = 0 Reorder the terms: -16w + 2x + 8y = 0 Solving -16w + 2x + 8y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2x' to each side of the equation. -16w + 2x + -2x + 8y = 0 + -2x Combine like terms: 2x + -2x = 0 -16w + 0 + 8y = 0 + -2x -16w + 8y = 0 + -2x Remove the zero: -16w + 8y = -2x Add '-8y' to each side of the equation. -16w + 8y + -8y = -2x + -8y Combine like terms: 8y + -8y = 0 -16w + 0 = -2x + -8y -16w = -2x + -8y Divide each side by '-16'. w = 0.125x + 0.5y Simplifying w = 0.125x + 0.5y
| 3x^2+21x-4x=218 | | Sinx=.8660 | | 2(x^2-4x-2)=0 | | 1/6k+2k=65/8 | | 2x^2+4x-12=x^2+4x+24 | | 10x-3x+20=4x+53 | | 3(5.4n+1)+5.6n=26.5 | | b/17-7b/17=12/17 | | 6b-2=10+3b | | -9(2-8)+4x+10=229 | | 8=3-5x | | 1+6x+5x=100 | | 7x(2+8)= | | -y=3x+6 | | -y^3x-2x^4y^3= | | 2y^2+4y-1=7y^2-7y+1 | | 378=(15+x)(12+x) | | d+99999999999999999990=999999999999999999 | | x+(x*4)=4 | | 12-2x=3x+22 | | 3.4c-1.2c=8.8 | | x-4/3+1=7/6 | | 5m+18=15-24-4m | | -k+2=-2k-2-4 | | 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 |